1976
DOI: 10.1056/nejm197601012940101
|View full text |Cite
|
Sign up to set email alerts
|

National Gonorrhea Therapy Monitoring Study

Abstract: To monitor the efficacy of the 1972 United States Public Health Service recommended treatment regimens for uncomplicated gonorrhea, we studied 9008 patients who were randomly assigned either to aqueous procaine penicillin G, 4.8 million units intramuscularly plus 1 g of oral probenecid, or to one of the three other recommended regimens. Among the 3871 patients re-examined within three to seven days after therapy, the penicillin-probenecid regimen was successful in 96.8 per cent, whereas the cure rates of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…gonorrhoeae have been reported to be cefamandole, cefoxitin, and cefuroxime (2,3,5,8,10,11). Our studies have confirmed that cefamandole and cefoxitin are effective in vitro against N. gonorrhoeae; however, HR 756 was much more active than either of these two antibiotics.…”
supporting
confidence: 72%
“…gonorrhoeae have been reported to be cefamandole, cefoxitin, and cefuroxime (2,3,5,8,10,11). Our studies have confirmed that cefamandole and cefoxitin are effective in vitro against N. gonorrhoeae; however, HR 756 was much more active than either of these two antibiotics.…”
supporting
confidence: 72%
“…Since the completion of the clinical study, we initiated a surveillance program to monitor the emergence of resistant strains to spectinomycin using sensitivity testing with 100 pg-spectinomycin disk and agar dilution. We have documented only a few sporadic (2) cases in a four year period, but a cautious approach to the widespreaduse of spectinomycin is recommended. Public health officials in the area must remain vigilant in their surveillance effort and be alert to the introduction or emergence of spectinomycin-resistant strain.…”
Section: Resultsmentioning
confidence: 99%
“…Oral regimens desirable for convenience, avoiding therapeutic injections and the need to store parentally administered drugs. Therapy came to include oral penicillin-like drugs (ampicillin and amoxicillin) which were widely preferred over injectable procaine penicillin/probenecid despite documentation of slightly lower treatment efficacy (1, 21). A four-day course of tetracycline had also been demonstrated 96.2% effective for uncomplicated gonorrhea in the National Gonorrhea Therapy Monitoring Study, but had the disadvantages of requiring patient medication adherence to complete the course of therapy and being contraindicated in pregnancy (21).…”
Section: Gonococcal Amr: a Continuous Processmentioning
confidence: 99%
“…These media provided an important tool to better define the high prevalence of gonorrhea and laid the groundwork for increased U.S. Public Health Service (USPHS) emphasis on gonorrhea control. Using recently developed Thayer-Martin medium, the National Gonorrhea Therapy Monitoring Study (initiated in 1972 by the USPHS’s CDC) systematically evaluated 4 regimens for gonorrhea therapy, confirming the efficacy of aqueous procaine penicillin G plus probenecid (96.8%), ampicillin plus probenecid (92.8%), tetracycline (96.2%) and spectinomycin (94.8%) (21). These studies provided validation for the first formal CDC recommendations for gonorrhea therapy which had been released in 1972 (1).…”
Section: Gonorrhea Diagnosismentioning
confidence: 99%